Nigella sativa as a potential therapy for the treatment of lung injury caused by cecal ligation and puncture-induced sepsis model in rats - Bayir, Y.; Albayrak, A.; Can, I.; Karagoz, Y.; Cakir, A.; Suleyman, H.; Uyanik, H.; Yayla, N.; Polat, B.; Karakus, E.; Keles, M. S. (Cellular and Molecular Biology, 2012)
We investigated the potential protective effects of Nigella sativa (NS) on mortality, serum levels of proinflammatory cytokines, oxidative stress and histopathological changes in lung tissues, in cecal ligation and puncture (CLP)-induced sepsis model in rats. Sepsis induction by CLP, determination of serum cytokine levels by ELISA, spectrophotometric determination of oxidative stress parameters, and histological examination of lung tissues. The rat groups were: 1) CLP group, 2) sham group, 3) NS500-sham group, 4) NS125, 5) NS250, 6) NS500 groups. NS treatment significantly decreased proinflammatory cytokine levels in serum; LPO level, MPO activity, and pathological changes in lung tissues, in CLP-induced sepsis, while significantly increasing GSH levels and SOD activity in the lung tissue. NS treatment after CLP potentially reduced mortality and may exert effects through the reduction in tissue oxidative stress and serum cytokines. The histopathological changes were minimized in lung tissue by NS, under sepsis conditions. We can suggest that NS reverses the systemic inflammatory reaction to polymicrobial sepsis and thereby reduces multiple organ failure. It may be suggested that role of the NS ethanolic extract in preventing formation of CLP induced sepsis, is due to the anti-inflammatory and antioxidant effects of the different compounds of the black seeds.